2007
DOI: 10.1177/00333549071220s207
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of Adult Hepatitis A and B Vaccination in STD Clinics and other Settings in New York State

Abstract: Since 1995, the New York State (NYS) Adult Hepatitis Vaccination Program has promoted adult hepatitis B vaccination for those receiving sexually transmitted disease (STD) clinic services. An average of 6,333 doses was administered annually from 1995 to 1999. By 2000, only 15 of 57 county STD programs in NYS outside of New York City participated. From 2000 to 2005, efforts to enroll county health departments and others included outreach, provision of hepatitis A and B vaccine, materials and training, and new co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
(6 reference statements)
0
6
0
Order By: Relevance
“…Five studies were found on hepatitis A and B combined vaccine, all from outside the EU/EEA. Of these, one study reported data on acceptance, uptake and acceptability [31], one on acceptance and uptake [32]) two on cost-effectiveness [33], [34]), one on accepatbility/barriers [35].…”
Section: Hepatitis a And B Combinedmentioning
confidence: 99%
See 1 more Smart Citation
“…Five studies were found on hepatitis A and B combined vaccine, all from outside the EU/EEA. Of these, one study reported data on acceptance, uptake and acceptability [31], one on acceptance and uptake [32]) two on cost-effectiveness [33], [34]), one on accepatbility/barriers [35].…”
Section: Hepatitis a And B Combinedmentioning
confidence: 99%
“…Another USA study evaluated a pilot program in which state-funded hepatitis vaccines were provided to local health departments to vaccinate jail inmates [32]. In two years, the number of county jails offering Two studies reporting on the cost-effectiveness of the combined hepatitis A/B vaccine interventions have been identified.…”
Section: Hepatitis a And B Combinedmentioning
confidence: 99%
“…Many of these studies, however, used convenience sampling from only one geographic area, and it has been almost a decade since data for the most recent of these studies were collected. In the interim, new programs integrating HBV vaccination into STD clinic services, HIV testing, and syringe exchange programs have been implemented as a way to increase HBV vaccination among gay and bisexual men and other high-risk adults 13-17. In this report, we characterize recent HBV vaccination rates among a national sample of gay and bisexual men.…”
mentioning
confidence: 99%
“…Recent programs have sought to overcome these obstacles and reach high-risk adults. Integration of HBV vaccination into STD clinic services, HIV testing, and syringe exchange programs has been mostly successful in increasing vaccination rates 13-17. One such program achieved 81% coverage (one or more doses) among men who have sex with men who were return clients to an STD clinic 14.…”
mentioning
confidence: 99%
“…For example, at its peak, the San Diego County STD hepatitis B vaccination project provided a first dose of hepatitis B vaccine to nearly 80% of eligible clients. 27 Other successful integration efforts documented in this supplement include (1) six STD clinics administering a median of 28 vaccinations per 100 client visits; [30][31][32] (2) widespread hepatitis A and B vaccination of adults by local health departments in New York State; 33 (3) statewide integration of hepatitis A and B vaccination and hepatitis A, B, and C counseling and testing in Florida public health clinics; 34 (4) statewide integration of hepatitis C counseling and testing in HIV/STD programs in Texas; 35 (5) a New York State program to improve continuity of hepatitis C antiviral therapy for inmates released from state prisons; 36 and (6) integration of hepatitis A and B vaccination for drug treatment program clients in Hartford, Connecticut. 37 Other reports in this supplement describe strategies to efficiently target and/or attract high-risk people for recommended services, including (1) a California HIV program wherein hepatitis C testing was shown to increase acceptance of HIV testing; 38 (2) a New York City STD clinic where IDUs accessing STD clinic services to get hepatitis C testing also accepted STD and HIV services, and new STDs and HIV infections were diagnosed and treated or referred; 39 (3) a study of positive anti-HCV tests among MSM who did not inject drugs compared with other men in three urban city STD and HIV programs; 14 and (4) an economic analysis of targeted anti-HCV testing in STD clinics.…”
Section: Lessons Learned From Integrating Viral Hepatitis Servicesmentioning
confidence: 99%